MARKERS OF INFLAMMATION AND IMMUNOLOGICAL COMPETENCE: ASSESSMENT IN THE EARLY POSTOPERATIVE PHASE OF CARDIAC SURGERY INVOLVING EXTRACORPOREAL CIRCULATION: Markers of inflammation and immunological competence - Mutevelić, Selma; Bajramović-Omeragić, Lejla; Šehić, Merima; Baljević-Spahić, Sumejja; Pehlivanović Kelle, Belma; Begović, Ermin; Hasanefendić, Berina; Mujičić, Ermina; Delić-Šarac, Marina; Batinić, Drago (Journal of Medical Biochemistry, 2025)
Background: To gain insight into the role and relevance of inflammatory and immunological markers in the comprehensive assessment of a patient’s immune response to surgical procedures. This study focused on investigating preoperative and postoperative serum levels dynamics of SAA, CRP, and proportion of HLA-DR+CD14+monocytes, CD14+ monocytes, and pro-inflammatory monocytes CD16+CD14+ in patients who underwent heart surgery using extracorporeal circulation (on-pump). Methods: An observational, prospective study was conducted at the Heart Center of the Clinical Center of the University of Sarajevo on 53 patients divided into 3 age groups: 50 – 59, 60 – 69, and 70 – 80. The serum levels of CRP and SAA were quantitatively determined by immunonephelometry. At the same time, flow cytometry technology was applied to measure the proportion of CD14+ monocytes, HLA-DR+CD14+monocytes, and pro-inflammatory CD16+CD14+ monocytes.Results: Measured values of CRP, SAA, proportion of monocytes CD14+, and proportion of pro-inflammatory monocytes CD16+CD14+ are significantly increased postoperatively compared to the preoperative values ​​(p
Keywords: extracorporeal circulation; C-reactive protein; serum amyloid A; monocytes